Annual Review of the Indian Primary Equity Market : 2019 – 20 - Gupta, Ambrish (Indian Journal of Research in Capital Markets, 2020)
This paper sought to carry out a comparative annual review of the Indian primary equity market for the year 2019 – 20 over 2018 – 19 and found that the year 2019 – 20 recorded a sharp recovery in the primary market in terms of resource mobilization. The paper covered aspects such as SEBI initiatives and policy changes in the primary market, global perspective of primary market, Indian perspective of the primary equity market, and market outlook for 2020 – 21. It concluded by stating that SEBI has brought well intended reforms in the primary market, which proved their fruitfulness during the year 2019 – 20. However, the onslaught of COVID - 19 in March 2020 almost put a break on the market activities. The future has become uncertain. The outlook for the rest of 2020 – 21 seems to be very bleak. Only the end of the COVID - 19 pandemic can bring back an enthused activity in the primary market.